A comprehensive and consistent mineral dissolution rate database: Part II: Secondary silicate minerals - Matylda Heřmanská; Martin J. Voigt; Chiara Marieni; Julien Declercq; Eric H. Oelkers (Chemical Geology, 2023)

First isolation of Vibrio tapetis and an atypical strain of Aeromonas salmonicida from skin ulcerations in common dab ( Limanda limanda ) in the North Sea - M Vercauteren; E De Swaef; A Declercq; L Bosseler; S Gulla; S Balboa; J L Romalde; L Devriese; H Polet; F Boyen; K Chiers; A Decostere (Journal of Fish Diseases, 2018)
Skin ulcerations rank amongst the most prevalent lesions affecting wild common dab ( Limanda limanda ) with an increase in prevalence of up to 3.5% in the Belgian part of the North Sea. A complex aetiology of these ulcerations is suspected, and many questions remain on the exact factors contributing to these lesions. To construct the aetiological spectrum of skin ulcerations in flatfish, a one‐day monitoring campaign was undertaken in the North Sea. Fifteen fish presented with one or more ulcerations on the pigmented and/or non‐pigmented side. Pathological features revealed various stages of ulcerations with loss of epidermal and dermal tissue, inflammatory infiltrates and degeneration of the myofibers bordering the ulceration, albeit in varying degrees. Upon bacteriological examination, pure cultures of Vibrio tapetis were retrieved in high numbers from five fish and of Aeromonas salmonicida in one fish. The V. tapetis isolates showed cross‐reactivity with the sera against the representative strain of serotype O2 originating form a carpet‐shell clam ( Ruditapes descussatus ). Moreover, the A. salmonicida isolates displayed a previously undescribed vapA gene sequence (A‐layer type) with possible specificity towards common dab. Further research is necessary to pinpoint the exact role of these agents in the development of skin ulcerations in common dab.

Sickeningly Sweet: L‐rhamnose stimulates Flavobacterium columnare biofilm formation and virulence - M D Lange; B D Farmer; A M Declercq; E Peatman; A Decostere; B H Beck (Journal of Fish Diseases, 2017)
Flavobacterium columnare , the causative agent of columnaris disease, causes substantial mortality worldwide in numerous freshwater finfish species. Due to its global significance and impact on the aquaculture industry continual efforts to better understand basic mechanisms that contribute to disease are urgently needed. The current work sought to evaluate the effect of L‐rhamnose on the growth characteristics of F. columnare . While we initially did not observe any key changes during the total growth of F. columnare isolates tested when treated with L‐rhamnose, it soon became apparent that the difference lies in the ability of this carbohydrate to facilitate the formation of biofilms. The addition of different concentrations of L‐rhamnose consistently promoted the development of biofilms among different F. columnare isolates; however, it does not appear to be sufficient as a sole carbon source for biofilm growth. Our data also suggest that iron acquisition machinery is required for biofilm development. Finally, the addition of different concentrations of L‐rhamnose to F. columnare prior to a laboratory challenge increased mortality rates in channel catfish ( Ictalurus punctatus ) as compared to controls. These results provide further evidence that biofilm formation is an integral virulence factor in the initiation of disease in fish.

Effect of 17β-estradiol on the in vitro differentiation of murine embryonic stem cells into the osteogenic lineage - S. Tielens; F. Wymeersch; H. Declercq; M. Cornelissen (In Vitro Cellular & Developmental Biology - Animal, 2008)